Perancangan Sistem Informasi Persediaan Bahan Baku Pada PT. Aneka Sarivita - Nur Azizah; Fakhirah Salsabila; Lutfy Rahayu (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2022)
The process of monitoring the inventory of raw materials in a company is very important. Because to find out the supply of raw materials that are still available, and so that there is no inhibition in the production process. But in fact, PT. Aneka Sarivita in recording raw material data still uses paper and is inputted using Microsoft Excel so that there is often a mismatch of the amount of raw material data with the amount in the warehouse. This system was built using PHP (Hypertext Preprocessor) as a programming language, MySQL as a database, Unified Modeling Language (UML) as a design method and SWOT (Strengths, Weaknesses, Opportunities, Threats) as an analysis method. The conclusion of this research is that a raw material inventory information system website is needed which aims to make the data search process accurate and the raw material inventory stock report can be controlled according to the raw material inventory in the warehouse. Keywords—Inventory; Raw materials; SWOT Proses monitoring persediaan bahan baku pada suatu perusahaan sangat penting. Karena untuk mengetahui persediaan bahan baku yang masih tersedia, serta supaya tidak terjadi penghambatan pada proses produksi. Namun pada kenyataanya, PT. Aneka Sarivita dalam pencatatan data bahan baku masih menggunakan kertas dan di input menggunakan Microsoft Excel sehingga sering terjadi ketidaksesuaian jumlah data bahan baku dengan jumlah yang berada di gudang. Sistem ini dibuat menggunakan PHP (Hypertext Preprocessor) sebagai bahasa pemrograman, MySQL sebagai database, Unified Modelling Language (UML) sebagai metode perancangan dan SWOT (Strengths, Weaknesses, Opportunities, Threats) sebagai metode analisa. Kesimpulan dari riset ini dibutuhkan sebuah website sistem informasi persediaan bahan baku yang bertujuan agar proses pencarian data menjadi akurat dan laporan stok persediaan bahan baku dapat terkontrol sesuai dengan persediaan bahan baku di gudang. Kata Kunci—Persediaan; Bahan baku; SWOT